NSD2 circular RNA promotes metastasis of colorectal cancer by targeting miR‐199b‐5p‐mediated DDR1 and JAG1 signalling - Chen, Liang‐Yan; Zhi, Zheng; Wang, Lian; Zhao, Yuan‐Yuan; Deng, Min; Liu, Yu‐Hong; Qin, Yan; Tian, Meng‐Meng; Liu, Yao; Shen, Tong; Sun, Li‐Na; Li, Jian‐Ming (The Journal of pathology, 2019)
Liver metastasis is the main cause of death in patients with colorectal cancer (CRC). Here, we searched for CRC metastasis‐associated circular RNA in a mouse model of liver metastasis of CRC by using RNA (transcriptome)‐sequencing. We identified a novel and conserved circular RNA, circ‐NSD2, functioning as a promoter of CRC metastasis. Circ‐NSD2 expression was elevated in CRC tissues and was markedly increased in advanced stages or metastatic tumours of CRC patients. Gain‐of‐function and loss‐of‐function experiments demonstrated that circ‐NSD2 promoted migration and metastasis of CRC in vitro and in vivo. Mechanistically, circ‐NSD2 acted as a sponge for the tumour suppressor miR‐199b‐5p and activated DDR1 (discoidin domain receptor tyrosine kinase 1) and JAG1 (Jagged 1) genes, which synergistically helped with cell–matrix interaction, migration and metastasis of CRC cells. Taken together, our findings highlight a novel oncogenic function of circ‐NSD2 and uncover a key mechanism for the circ‐NSD2/miR‐199b‐5p/DDR1/JAG1 axis in CRC metastasis, which may serve as a prognostic factor and therapeutic target for antimetastatic therapy in CRC patients. Copyright © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.